Herpes Zoster on a bladder cancer patient – a rare case - Dhelya Widasmara; Adya Sitaresmi; Santosa Basuki; Besut Daryanto; Kurnia Penta Seputra (Surgical Residency Program Syiah Kuala University, 2022)
Introduction: Herpes zoster (HZ) is caused by reactivation of latent varicella-zoster virus (VZV) infection due to disturbance in T-cell mediated immunity. Risk factors include malignancy and therapy related to malignancy. Bladder cancer has a moderate association with HZ, with a risk increment of 10-50%. The rate of HZ in bladder cancer patients is 8/1000. Case description: A 57-years-old man with bladder cancer T4bN3M0 complained of a painful erythematous vesicular rash on the left front abdomen extended to the back 1 week prior, accompanied by fever and burning sensation. He has had regular chemotherapy using Gemcitabine and Cisplatin, and radiotherapy with 2 Gray doses each session. Dermatological examination showed multiple well-defined erythematous-based vesicles, clustered on the left abdominal, flank, and posterior thorax region at T7-T9 dermatome. Tzanck-smear examination showed multinucleated giant cells. The patient was given acyclovir, paracetamol, and wet dressing on vesicles. His chemoradiotherapy was also halted. On the 7th day of evaluation, there were no new lesions and his complaints improved. In cancer patients, CD4+ and CD8+ levels decreased, accompanied by lymphocyte proliferation impairment. Cytotoxic chemotherapy agents work by attacking proliferation cells, affecting immune-related cells. Ion radiation in radiotherapy interferes with a regional cellular immune response that inhibits viral reactivation. Conclusion: Principal HZ management in cancer patients includes antiviral and analgesics. In cancer patients, the occurrence of HZ can disturb and postpone management related to malignancy. The postponement of chemoradiotherapy is based on the patient's conditions and the severity of the disease.